Cook's Role in Hygiene and Sanitation Improvement in Hot Kitchen at Ascent Premiere Hotel Malang - Arityas, Gita; Faozen, Faozen (Indonesian Journal of Microbiology, 2024)
This study was undertaken to learn how the kitchen management at Ascent Premiere Hotel Malang attempts to improve the level of cleanliness and sanitation. The study method employed is a qualitative descriptive approach, with data collected through observation, interviews, and recording. The research subjects are sous chefs and junior sous chefs who can supply research-related information. The goal of this study is to focus on efforts to improve kitchen cleanliness and sanitation in order to provide a sense of security, comfort, and job efficiency for all staff members. According to the study's findings, several employees expressed dissatisfaction with the maximum execution of hygiene and sanitation requirements due to the low quality of the standard operating procedures (SOP) that were implemented. To address these problems, the cooks took immediate action by expanding the number of personnel, holding daily briefings before work, and doing other things that can help improve the hygiene and sanitation at the Ascent Premiere Hotel Malang kitchen.